Comparison of dacryocystography and lacrimal scintigraphy in the diagnosis of functional nasolacrimal duct obstruction. Issue 9 (1st September 1999) - Wearne, Michael J; Pitts, John; Frank, John; Rose, Geoffrey E
Abstract : AIM: It appears from the literature that no standardised examination exists for patients with functional nasolacrimal duct obstruction. The role of dacryocystography and lacrimal scintigraphy was compared in the diagnosis and management of these patients. METHOD: Patients who were clinically diagnosed as having unilateral or bilateral functional nasolacrimal duct obstruction were prospectively entered into the study and data collected over 12 months in Moorfields Eye Hospital and Whipps Cross Hospital, London. All cases had, on separate occasions, a standardised dacryocystogram with delayed erect films and a lacrimal drainage scintigram. RESULTS: 45 lacrimal systems of 32 patients (mean age 62 years; 59% male) fulfilled the inclusion criteria. Abnormalities were detected with dacryocystography in 93% of systems and with lacrimal drainage scintigraphy in 95% of systems. Based on the results of previous quantitative studies, the positive scintigrams were subdivided into those demonstrating prelacrimal sac delay (13%), delay at the lacrimal sac/duct junction (35%), or delay within the duct (47%). Combining the two imaging techniques increased the sensitivity to 98%. CONCLUSIONS: Both investigations are very sensitive at detecting abnormalities in patients with a clinical diagnosis of functional nasolacrimal duct obstruction. Lacrimal drainage scintigraphy is a slightly more sensitive test, but missed an abnormality detected by dacryocystography in two (4%) systems. A combination of the two techniques gives the highest sensitivity with maximum anatomical and physiological information but, in clinical practice, it is reasonable to perform a dacryocystogram initially and proceed to scintigraphy only if contrast radiography is normal.